PENGARUH LABA AKUNTANSI, KOMPONEN ARUS KAS DAN SIZE PERUSAHAAN TERHADAP RETURN SAHAM (Study Kasus Perusahaan LQ-45 Di Bei Tahun 2013-2017) - Novi Darmayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
This study aims to provide empirical evidence of the influence of published financial statement information, namely accounting earnings, cash flow components that consist of cash flows from operating activities, cash flows from investing activities and cash flows from financing activities and company size on stock returns in the company index of LQ-45 listed on BEI. This study uses the observation period 2013-2017, with purposive sampling method obtained 13 emitter samples. Statistical methods used to analyze data using multiple regression analysis. The variables used are accounting earnings, cash flow components, namely Operating Cash Flow, Investment Cash Flow, Cash Flow Funding and company size as independent variables, while Stock Return is the dependent variable. From testing the hypothesis, resulting in the findings that the variable accounting earnings have a significant positive influence on stock returns, variable Operating Cash Flow, Investment Cash Flow, Cash Flow Funding does not have the significant influence on stock returns and company size does not have a significant effect on stock returns.